Fiqh Siyasah in Indonesia’s Post-colonial Era: Between Classical Doctrines and Contemporary Practices - Maula, Bani Syarif (Jurnal Syariah dan Hukum Komparatif, 2025)
This study examines contemporary understandings of Fiqh Siyasah—a branch of Islamic legal thought concerned with governance and political relations—within Islamist movements in post-Reformasi Indonesia. Fiqh Siyasah contains foundational principles that govern the relationship between the state and its citizens, as well as between Muslims and non-Muslims. Despite its significance, Fiqh Siyasah has seen limited application in the modern era, particularly after the imposition of Western legal systems during the colonial period. The research explores how post-colonial Islamist groups interpret legal provisions within Fiqh Siyasah, with a specific focus on doctrines related to war (harb) and peace (sulh). This focus is especially relevant given recurring societal tensions triggered by demands for the implementation of Sharia law by certain Islamic groups. Utilizing a qualitative methodology and a process tracing approach, the study finds that Muslim interpretations of Qur’anic verses pertaining to conflict and relations with non-Muslims are diverse and often context-dependent. While many Islamist groups share a common ideological aim of establishing Sharia law, their strategies and theological positions vary significantly. Not all are radical in orientation, and not all radical organizations adhere to the doctrine of dividing the world into dār al-Islām (abode of Islam) and dār al-harb (abode of war). These findings highlight the complexity and internal plurality of contemporary Islamic political thought in Indonesia.